Analysis of the results of theoretical seismograms mathematical designing - MALYTSKYI, D.; KOZLOVSKYI, E.; KHYTRIAK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The software for the seismic wave field modeling on a free surface of a layered half-space using the Tompson-Haskell method and 6-th order matrices is suggested. The seismic-wave source is located in the homogeneous isotropic layer and is represented by seismic moment tensor. The results of mathematical modeling are sufficiently simple for utilization and can be used for interpretation of seismic records. On the example of the 11.07.2001 earthquake with m=2,3 the possibility of applying of the software for solving of seismology inverse problem of the seismic moment tensor’s components determination with one station data using was shown.